Vitamin B12 Deficiency Alters the Gut Microbiota in a Murine Model of Colitis - Lurz, Eberhard; Horne, Rachael G.; Määttänen, Pekka; Wu, Richard Y.; Botts, Steven R.; Li, Bo; Rossi, Laura; Johnson-Henry, Kathene C.; Pierro, Agostino; Surette, Michael G.; Sherman, Philip M. (Frontiers in Nutrition, 2020)
Purpose: Inflammatory bowel disease (IBD) refers to a spectrum of autoimmune diseases, which result in chronic intestinal inflammation. Previous findings suggest a role for diet, nutrition and dysbiosis of the gut microbiota in both the development and progression of the condition. Vitamin B12 is a key cofactor of methionine synthase and is produced solely by microbes. Previous work links increased levels of homocysteine, a substrate of methionine synthase, MetH, to IBD indicating a potential role for vitamin B12 deficiency in intestinal injury and inflammation. This study assessed the role of vitamin B12 in shaping the gut microbiota and determining responses to intestinal injury using a reproducible murine model of colitis. Methods: The effects of vitamin B12 supplementation and deficiency were assessed in vivo; 3-week-old post-weanling C57Bl/6 mice were divided into three dietary treatment groups: 1) sufficient vitamin B12 (50mg/Kg), 2) deficient vitamin B12 (0mg/Kg) and 3) supplemented vitamin B12 (200mg/Kg) for a period of 4 weeks. Intestinal injury was induced with 2% dextran sodium sulphate (DSS) via drinking water for 5 days. The impact of varying levels of dietary vitamin B12 on gut microbiota composition was assessed using 16S rRNA gene sequencing from fecal samples collected at day 0 and day 28 of the dietary intervention, and 7 days following induction of colitis on day 38, when blood and colonic tissues were also collected. Results: No significant alterations were found in the gut microbiota composition of disease-free animals in response to dietary interventions. By contrast, after DSS-induced colitis, >30 genera were significantly altered in vitamin B12 deficient mice. Altered B12 levels produced no significant effect on composite disease-activity scores; however, administration of a B12 deficient diet resulted in reduced DSS-induced epithelial tissue damage. Conclusions: Vitamin B12 supplementation does not alter the gut microbiota composition under healthy conditions, but does contribute to differential microbial responses and intestinal dysbiosis following the induction of experimental colitis.